2015
DOI: 10.4321/s1137-66272015000100010
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de las intervenciones familiares en centros geriátricos: una revisión sistemática

Abstract: revisiones0 efectividad de las intervenciones familiares en centros geriátricos. Una revisión sistemática Effectiveness of family interventions in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Therefore, families must be included as another vital piece in the healing process for future pandemic situations. It is known that interventions that consider the family as a caring unit positively impact health for both patients and family caregivers (Villanueva Lumbreras et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, families must be included as another vital piece in the healing process for future pandemic situations. It is known that interventions that consider the family as a caring unit positively impact health for both patients and family caregivers (Villanueva Lumbreras et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, while there is a consensus on the importance of the implication and adaptation of the relative ( Crawford et al., 2015 ), research on the subject has been scarce in the Latin American context, and we have not found any study conducted from a transcultural approach. Villanueva-Lumbreras et al. (2015) published a systematic review that identified effective interventions to help families during the institutionalization process at a nursing home.…”
Section: Introductionmentioning
confidence: 99%